Chemical Pulps for Writing and Printing Papers from Eucalyptus citriodora - Guha, S. R. D.; Prasad, B. D. (Indian Forester, 1961)
Laboratory experiments on production of chemical pulps from Eucalyptus citriodora for writing and printing papers by sulphate process are described. The average fibre length of the pulp was 1.03 mm and the average fibre diameter was 0.014 mm. Easy bleaching pulps in good yield with satisfactory strength properties could not be prepared. The investigation reported in this paper has shown that the suitability of EucaLyptus citriodora as a fibrous raw matreial for the manufacture of white writing and printing papers will depend on raw material costs as the bleach consumption is high and yields are not quite good.